2015
DOI: 10.1111/evj.12333
|View full text |Cite
|
Sign up to set email alerts
|

Dominant components of the Thoroughbred metabolome characterised by 1H‐nuclear magnetic resonance spectroscopy: A metabolite atlas of common biofluids

Abstract: Metabonomics provides a platform for investigating complex and dynamic interactions between the host and its consortium of gut microbes and has the potential to uncover markers for health and disease in a variety of biofluids. Inherent variation in faecal extracts along with the relative abundance of microbial-mammalian metabolites in urine and invasive nature of plasma sampling, infers that urine is the most appropriate biofluid for the purposes of metabonomic analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 58 publications
1
42
0
1
Order By: Relevance
“…In the category of animal products, bovine-based studies had the most articles published (16 articles) relative to all other groups. Some of the more interesting applications of metabolomics found in our survey include the use of metabolomics for quality control of animal products [46; 47], evaluating nutritional value and impact of various feed sources on animal health and products [25], investigating disease biology by using animal models of human disease [48; 49], investigation of potential metabolite biomarkers of animal disease [22; 23], assessment of production traits [50; 51], reproductive performance [29], and general metabolome characterization [52; 53]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the category of animal products, bovine-based studies had the most articles published (16 articles) relative to all other groups. Some of the more interesting applications of metabolomics found in our survey include the use of metabolomics for quality control of animal products [46; 47], evaluating nutritional value and impact of various feed sources on animal health and products [25], investigating disease biology by using animal models of human disease [48; 49], investigation of potential metabolite biomarkers of animal disease [22; 23], assessment of production traits [50; 51], reproductive performance [29], and general metabolome characterization [52; 53]. …”
Section: Resultsmentioning
confidence: 99%
“…Clark et al [89] reported 97 metabolites out of the 571 detected features in caprine serum using a combination of both GC-MS and LC-MS. In equine metabolomics, the highest number of metabolites identified was from a study conducted by Escalona and colleagues [53] with 102 metabolites identified via NMR analysis of plasma, urine and fecal water. A porcine metabolomics study by Metzler-Zebeli et al [90] reported 104 out of 132 detected serum metabolites using LC-MS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LEfSe (Segata et al, 2011) was used to identify differentially abundant OTUs. Bacterial metabolic profiles were characterized by 1 H NMR spectroscopy (Escalona et al, 2015), from urine, analysed by Principal Components Analysis. Fermentation of hay and oats, separately, were measured by in vitro gas production (Murray et al, 2006), data were analysed by repeated measures ANOVA.…”
Section: Objectivesmentioning
confidence: 99%
“…Metabolomics is a powerful systems biological approach that simultaneously measures all metabolites present within biological fluids or tissues . Metabolite phenotypic profiling captures relationships of the cellular processes they represent.…”
Section: Introductionmentioning
confidence: 99%